Impacts of climate change on heating and cooling degree‐hours over China. (22nd October 2020) - Shi, Ying; Han, Zhenyu; Xu, Ying; Xiao, Chan
Abstract: Based on hourly temperature data collected from 2, 307 meteorological stations over China and two sets of climate change simulations over East Asia using the regional climate model version 4.4 (RegCM4.4) driven by the global models of HadGEM2‐ES and MPI‐ESM‐MR, future changes of heating and cooling degree‐hours (HDH and CDH) at the end of the 21st century under RCP4.5 scenario are investigated. Compared against the observation, the spatial distribution, magnitude and annual cycle of present‐day HDH and CDH at different times, as well as the diurnal cycle of them can be realistically simulated by the model. Meanwhile, some bias can also be found and it varies with the times, especially for CDH. At the end of the century, significant decrease of HDH can be found over the Tibetan Plateau, the northern part of Northeast China, and Northwest China at each times while increase of CDH are observed at all the times except some parts of the Tibetan Plateau where the CDH remains zero due to the cold climate there. But for different times, some differences are found in HDH decrease and CDH increase. For example, the changes of HDH at the fifth to the seventh times present a weaker decrease in the northwestern basins compared to other times and the CDH increase are more significant at the fifth and the sixth times. The regional mean changes of HDH and CDH over China in the 21st century (2006–2098) also diverge among different times, which indicates the degree‐hours is needed to precisely calculate the hourly heating and cooling energy demand and then the heating and cooling degree days. Abstract : 1. Significant decrease of HDH can be found over the Tibetan Plateau, the northern part of Northeast China, and Northwest China at each time.2. Increase of CDH is observed in all the times except some parts of the Tibetan Plateau where the CDH remains zero due to the cold climate there.3. The largest decease of HDH can be found at the second time (5 a.m.) while the CDH increase is more significant at the fifth and the sixth (2 p.m. and 5 p.m.) times.